Fatigue damage of monolithic posterior computer aided designed/computer aided manufactured crowns. Issue 3 (July 2019) - Schlenz, Maximiliane Amelie; Schmidt, Alexander; Rehmann, Peter; Wöstmann, Bernd
Abstract: Purpose: To analyse fatigue damage of monolithic computer-aided-designed/computer-aided-manufactured (CAD/CAM)-materials after loading with high masticatory forces in standardized posterior crowns in a mouth-motion-simulator. Methods: For manufacturing of test specimens (5 groups, 16 specimens each), two corresponding Standard-Tessellation-Language-(STL)-data-sets (one for the teeth and one for the crowns) were designed. The teeth were CAD/CAM-milled of human third molars and the crowns of three different CAD/CAM composite blocks (Lava Ultimate, 'LU'; Brilliant Crios'BC'; Cerasmart, 'CS'), one polymer-infiltrated-ceramic network (Vita Enamic, 'VE') and a control group of lithium disilicate ceramics (IPS e.max CAD, 'EM'). Crowns were adhesively cemented with their corresponding luting system on the human teeth. Half of the specimens were light-cured ('LC') and the others were chemical-cured ('CC'). A mouth-motion-simulator (WL-tec, 2 Hz, 37 °C) applied dynamic cyclic loading between 50–500 N for a period of 1 million cycles. Afterwards, a dye penetration test (aqueous basic-fuchsine) revealed damage of test specimens. Each specimen was sectioned into four equidistant slices and the area without damage was measured with a digital microscope (Zeiss) and radial cracks at the cementation surface were assessed. Data were subjected to Tukey's test. Results: All specimens showed fatigue damage in the occlusal contact area. LU, BC and CS exhibited a significant greater area without damage compared to VE and EM (p < .05). EM and VE showed additional radial cracks at the cementation interface in both curing modes, whereas LU, BC and CS showed only radial cracks with chemical-cured luting cement. Conclusions: Monolithic CAD/CAM composite crowns showed significantly lower fatigue damage, particularly if the luting system was light-cured.